Magnoflorine Enhances LPS-Activated Pro-Inflammatory Responses via MyD88-Dependent Pathways in U937 Macrophages - Haque, Md. Areeful; Jantan, Ibrahim; Harikrishnan, Hemavathy; Abdul Wahab, Siti Mariam (Planta Medica, 2018)
Magnoflorine, a major bioactive metabolite isolated from Tinospora crispa, has been reported for its diverse biochemical and pharmacological properties. However, there is little report on its underlying mechanisms of action on immune responses, particularly on macrophage activation. In this study, we aimed to investigate the effects of magnoflorine, isolated from T. crispa on the pro-inflammatory mediators generation induced by LPS and the concomitant NF-κB, MAPKs, and PI3K-Akt signaling pathways in U937 macrophages. Differentiated U937 macrophages were treated with magnoflorine and the release of pro-inflammatory mediators was evaluated through ELISA, while the relative mRNA expression of the respective mediators was quantified through qRT-PCR. Correspondingly, western blotting was executed to observe the modulatory effects of magnoflorine on the expression of various markers related to NF-κB, MAPK and PI3K-Akt signaling activation in LPS-primed U937 macrophages. Magnoflorine significantly enhanced the upregulation of TNF-α, IL-1β, and PGE2 production as well as COX-2 protein expression. Successively, magnoflorine prompted the mRNA transcription level of these pro-inflammatory mediators. Magnoflorine enhanced the NF-κB activation by prompting p65, IκBα, and IKKα/β phosphorylation as well as IκBα degradation. Besides, magnoflorine treatments concentration-dependently augmented the phosphorylation of JNK, ERK, and p38 MAPKs as well as Akt. The immunoaugmenting effects were further confirmed by investigating the effects of magnoflorine on specific inhibitors, where the treatment with specific inhibitors of NF-κB, MAPKs, and PI3K-Akt proficiently blocked the magnoflorine-triggered TNF-α release and COX-2 expression. Magnoflorine furthermore enhanced the MyD88 and TLR4 upregulation. The results suggest that magnoflorine has high potential on augmenting immune responses.
Keywords: magnoflorine; Tinospora crispa; Menispermaceae; immunomodulation; MyD88; NF-κB; MAPKs; Akt